Effects of Sublethal Temperature Stress on the Growth, Survival and Culturability of Listeria Monocytogenes - Lani, Mohd Nizam (2002)
Survival and growth of Listeria monocytogenes L56 (JMR isolate) was studied in trypticase soy broth grown at 37°C before being subjected to three selected sublethal stress of temperatures (55°C, 28°C and 4°C) using log and stationary phase as inoculums using two-plating systems; TSA with and without 4% NaCl (TSAS). The influence of morphological changes and listerial motility as affected by sublethal stress of temperatures were also determined using Scanning Electron Microscopy (SEM) and motility media, respectively. A standard growth curve of L. monocytogenes at 37°C was established using plate counts showed that the log and stationary phase of the organism were achieved after 12 and 19 hours, respectively. It was observed that viable bacterial population (CFU/ml) after log and stationary phase were 108 and 109, respectively. From the growth curve, the generation time of L. monocytogenes at 37°C was 60 min. The bacterial growth rates obtained from culturability on culture plates assessed using two-system media, TSA with and without 4% NaCl concentration (TSAS) were assessed by their generation time. Cells of L. monocytogenes grown in exponential phase cultures demonstrated biphasic survival curves at 55°C and 4°C in both media. In contrast, survival curves at 28°C were not biphasic. The growth rates of L. monocytogenes grown in stationary phase cultures were also assessed by their generation time. The addition of sodium chloride enhanced heat resistance of microorganism. It has been proven that biphasic curve and tailing with/without shoulder from thennal inactivation curves in this study were associated with the occurrence of microbial injury. During the exponential phase of L. monocytogenes, the percentage injury at 55°C, 28°C and 4°C were ranged between 3.21% to 28.49%, 2.47% to 4.38%, and 4.34% to 8.61%, respectively. Whilst, during the stationary phase of L. monocytogenes, the percentage injury at 55°C, 28°C and 4°C were ranged between 2.05% to 4.15%, 1.44% to 3.06%, and 1.07 to 4.25%, respectively. L. monocytogenes cells were able to survive throughout the sublethal stress of temperatures and undergone morphological changes to adapt to new temperatures. In this study, results from Scanning Electron Microscopy (SEM) revealed three different analyses of temperature-stressed cells which were average mean of cells length, distribution of cells length, and minimum versus maximum cells length. The study demonstrated cells of both log and stationary phase showed a significant variation of morphology. Cells of log phase became elongated only at 55°C, not at 28°C and 4°C whereas cells of stationary phase were shorter and more coccoidal rather than elongated as in log phase cells. However, cells at 28°C were more intact than cells at other temperatures for most of the observations. In conjunction with SEM results, the variation of listerial morphology and the effect of listerial motility would be a part of microbial adaptation towards sublethal stress of temperatures. The loss of motility in stationary phase cells strongly suggested that listerial motility play a role in survival of the organism under temperature stress. The stationary phase cells of L. monocytogenes were more resistant than exponential phase cells exhibited by increased of generation times, lower percentage injury and most of the cells became coccoid.